Removal of Organic Matters, Phosphates and Nitrates Present in Dairy Industrial Wastewater Using Jujube Seeds Biocoagulant (International Journal of Environmental Sciences, 2025)
This study aims to remove of organic matter, nitrate and phosphate present in industrial wastewater from a dairy facility in Bechar Algeria using the coagulation–sedimentation process. A natural coagulant based on jujube seed powder (Zizyphus lotus) was tested. Jar Test experiments were conducted to study the effect of various doses on pH, conductivity, COD, TSS, nitrates, and phosphates.The results showed that the natural coagulant is effective, achieving removal efficiencies of: COD (90%), TSS (87.5%), NO₃⁻ (98.5%), PO₄³⁻ (70%) and OM (33.2%) at an optimal dose of 2.5 g/L without pH adjustment. Thus, jujube seed powder is a promising eco-friendly and cost-effective alternative for industrial wastewater treatment.